QED the strange theory of light and matter - Feynman, Richard P. (Hyderabad Universities Press, 1985)
This book is a straightforward, honest explanation of a rather difficult subject-the theory of quantum electrodynamics for a nontechnical audience. It is designed to give the interested reader an appreciation for the kind of thinking that physicists have resorted to in order to explain how Nature behaves. It is a record of the lectures on quantum electrodynamics given at UCLA by Richard Feynman. If you are planning to study physics (or are already doing so), there is nothing in this book that has to be (3z(Bunlearned(3y(B: it is a complete description, accurate in every detail, of a framework onto which more advanced concepts can be attached without modification. For those of you who have already studied physics, it is a revelation of what you were really doing when you were making all those complicated calculations.s
Keywords: Quantum electrodynamics; Electrons; Photons